Estudio comparativo in vitro del grado de microfiltración de dos materiales provisionales en molares y premolares permanentes - Rosales Chamba, Yovana Elizabeth (2019)
Oral health professionals often resort to various types of provisional materials as a temporary option in their treatments, but there are clinical manifestations that demonstrate the lack of airtight seal resulting in marginal filtration which leads to contamination of the dental structure. Objective: To compare the degree of microfiltration of two temporary materials in permanent molars and premolars by means of methylene blue staining. Materials and methods: 40 healthy unirradicular and multiradicular teeth were used, divided into a control group of 20 teeth, designated with a C1-20 code and 20 dental pieces for an experimental group identified with the O1-20 code; to be placed in the incubator (Thermo Scientific model HERA THERM IGS60) at 37 ° C temperature for 7 days; after that, these were immersed in methylene blue for 7 days, then cut longitudinally and the degree of microfiltration was evaluated in each of them using a Lee score scale: from 0 to 3 versus the microscope (Single Model Binocular Steromicroscope ZM181HF, 10X magnification eyepieces and 6.7.1) zoom. Results showed that Coltosol F was the temporary restoration material that presented the lowest degree of microfiltration reaching the dentin enamel junction (grade 3) with a percentage of 65%. Concluding that the material of choice in clinical practice, according to the present study, is Coltosol, because it has a lower degree of microfiltration, grade 1, unlike the Obetur with a higher degree of microfiltration, grade 2, and even achieving results. With grade 3. Key words: marginal micro filtration, temporary sealing materials.